2018
DOI: 10.3390/s18103490
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Noise Covariance Matrices to Improve Orientation Estimation by Kalman Filter

Abstract: Magneto-inertial measurement units (MIMUs) are a promising way to perform human motion analysis outside the laboratory. To do so, in the literature, orientation provided by an MIMU is used to deduce body segment orientation. This is generally achieved by means of a Kalman filter that fuses acceleration, angular velocity, and magnetic field measures. A critical point when implementing a Kalman filter is the initialization of the covariance matrices that characterize mismodelling and input error from noisy senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 28 publications
0
8
0
3
Order By: Relevance
“…Adaptive gain tuning of filters Nez et al [32] showed that the filter gains must be selected carefully, or the filter performance could deteriorate. Also, Nez et al [32] showed that the values of the gains identified through an optimization were different from those obtained by the Allan Variance method [33]. The reason could be that the optimized gains implicitly account for error sources such as modelling or calibration [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive gain tuning of filters Nez et al [32] showed that the filter gains must be selected carefully, or the filter performance could deteriorate. Also, Nez et al [32] showed that the values of the gains identified through an optimization were different from those obtained by the Allan Variance method [33]. The reason could be that the optimized gains implicitly account for error sources such as modelling or calibration [32].…”
Section: Resultsmentioning
confidence: 99%
“…Also, Nez et al [32] showed that the values of the gains identified through an optimization were different from those obtained by the Allan Variance method [33]. The reason could be that the optimized gains implicitly account for error sources such as modelling or calibration [32]. Therefore, to conduct a fair comparison and provide reliable results, we optimized the gains of all filters, according to [28].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the error calculated in Equation ( 39 ), a rule was created to determine the error condition for switching to different values of the measurement error covariance. The covariance value of the measurement error indicates the degree to which the system relies on the gyroscope prediction or magnetometer data to estimate the heading [ 24 ]. If a severe magnetic disturbance is detected, a big measurement error covariance value is selected to prevent the effect of erroneous sensor data on the estimate.…”
Section: Attitude and Heading Estimation With Ekf-based Sensor Fusionmentioning
confidence: 99%
“…In this case, the extended KF can be used for estimating the three-dimensional orientation of a rigid body [18,19]. Furthermore, the multi view human pose estimation process is described in [20][21][22]. For determining heart rate, 2 Motion Capture Systems Using Optimal Signal Processing Algorithm: A State-of-the-art Literature a KF algorithm is used in [23,24].…”
Section: Literature Reviewmentioning
confidence: 99%